The Impact of Additional Taxation of Part-Time Employment Contracts in the Romanian Economy Against the Background of an Accumulation of Recessions - Antonia-Cătălina HORVAT (CECCAR Business Review, 2023)

(untitled)
For the business entities, especially for micro-entities, the year 2022 has represented an economic collapse due to fiscal changes. One of the most controversial measures adopted by the Government aims overtaxing of the employees who obtain income based on a part-time individual employment contract. The article hereby aims to draw attention to the impact of the Fiscal Code changes on the income from salaries for the part-time employment contracts, changes overlapped against the background of the world energy crisis and the military crisis at the Romanian border.